2016
DOI: 10.5688/ajpe809159
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Curricular Improvement Based on Evaluation of Student Performance on Milestone Examinations

Abstract: Objective. To identify and address areas for curricular improvement by evaluating student achievement of expected learning outcomes and competencies on annual milestone examinations. Design. Students were tested each professional year with a comprehensive milestone examination designed to evaluate student achievement of learning outcomes and professional competencies using a combination of multiple-choice questions, standardized patient assessments (SPAs), and objective structured clinical examination (OSCE) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…This model is also the first to include a midpoint evaluation, as other studies have only explored the Pharmacy Curriculum Outcomes Assessment (PCOA), which is analogous to a midpoint assessment across pharmacy schools in the United States [ 24 , 26 ]. Additionally, it suggests potential curriculum revisions to optimize student success, such as re-evaluating course weight, structure, and assessments based on identified associations, particularly courses with inverse relationships to performance in clinical rotations and the PEBC Pharmacist Qualifying Examination [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is also the first to include a midpoint evaluation, as other studies have only explored the Pharmacy Curriculum Outcomes Assessment (PCOA), which is analogous to a midpoint assessment across pharmacy schools in the United States [ 24 , 26 ]. Additionally, it suggests potential curriculum revisions to optimize student success, such as re-evaluating course weight, structure, and assessments based on identified associations, particularly courses with inverse relationships to performance in clinical rotations and the PEBC Pharmacist Qualifying Examination [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent any variables of particular interest from being eliminated by backward selection, the research team identified critical courses/inputs and ensured their inclusion in the model. The following were selected based on a consideration of those that had demonstrated statistically significant correlations with certain entry-to-practice milestones in the published literature, and those that are compulsory components of the curriculum with direct applicability to the provision of patient care [ 8 , 9 , 10 , 12 , 13 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]: Integrated Patient-Focused Care series courses: PHARM 220, 221, 222, 223, 320, 321, 323, 324, and 422; Professional Practice series courses: PHARM 129, 130, 228, 229, 329, and 330; Pharmacokinetics: PHARM 224; Co-op work-term scores; PharmD rotation scores; Midpoint assessment MCQ scores; Year 1, 2, 3, and 4 OSCE scores. …”
Section: Methodsmentioning
confidence: 99%